Integrasi Pembelajaran Berbasis Proyek ke Pembelajaran Mata Kuliah Manajemen Pendidikan - Khodijah, Siti (Indo-MathEdu Intellectuals Journal, 2025)
Educational management courses are generally taught with a theoretical approach or field studies of the implementation of governance in schools, then students prepare reports. However, in certain conditions, learning educational management is not possible through empirical studies. This study aims to integrate project-based learning (PjBL) strategies in teaching educational management courses to qualitatively see student learning outcomes. This study is a type of qualitative research with data sources from students participating in the Educational Management course. Through the Spraedly analysis technique, this study shows that in practice the learning outcomes of educational management courses have been achieved in the sense that they show learning outcomes as expressed by C. Van Parreren and Robert M. Cagne, namely first, in general students are skilled at designing school governance needs by implementing the POAC function which can be assumed to be able to carry out these skills in practice. Second, specifically students have soft skills in working in teams or groups openly seeing the trends of challenges in educational management practices in schools, describing their ideas and skills. PjBL. PjBL can be an alternative to the empirical approach.